Pemberdayaan Ekowisata Berbasis Kearifan Lokal - Encep Andriana; Rina Yuliana; Wardatul Ilmiah; Callista Aulina; Tri Esti Noviyanti; Suci Ramadayanti (Jurnal Pemberdayaan Masyarakat, 2022)
The service is carried out to empower the community through the development of ecotourism based on local wisdom. The local wisdom contained in Wanasari Village is the natural potential of the tea garden. This service activity uses counseling, training, and simulation methods aimed at community groups. Training activities are carried out to increase the income of the village community as well as publicize tea garden tours with the concept of utilizing local potential and wisdom. The method of activity is by carrying out community empowerment programs based on local wisdom, which consists of three fields, namely economic, organizational, and social. The results obtained through the implementation of this service are increasing the level of public knowledge about ecotourism development. Local wisdom in Wanasari Village has been explored and utilized for ecotourism development materials.